Pengembangan Lembar Kerja Siswa (LKS) Etnomatematika Berbasis Penemuan Terbimbing pada Materi Bangun Ruang Sisi Datar - Anggeraini Oktarina; Maria Luthfiana; Rani Refianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to develop student work ethics-oriented student worksheets based on guided discoveries on the material of flat side space and to find out the quality of worksheets developed in terms of validity, practicality and potential effects. The method, this research is Research and Dependency (R&D), that is development research that refers to a modified 4-D development model. The instruments used to measure the quality of worksheets developed include validation sheets, practicality questionnaires, walkthroughs and tests. Worksheets that are developed are valid based on validation sheets by experts and are practical based on a practical questionnaire. The potential effects of worksheets developed can be seen from the activities and understanding of students in working on the problems given to the worksheets. The results showed that: (1) the quality of worksheets seen from the aspect of validity included in the valid category with an average score of 3.18; (2) the quality of worksheets seen from the practical aspect is categorized practically with an average score of 3.24; and (3) worksheets have a potential effect on student learning outcomes where 20 students (76.9%) are included in the category of completion while there are 6 students (23.1%) have not been completed with the Minimum Learning Completion (KBM) specified. Conclusion, ethnomatematics-oriented worksheet based on guided discovery developed is declared valid, practical and potential in improving student learning outcomes in the material of flat side spaces. Keywords: Ethnomatematics, LKS, Guided Discovery